IPTEKS IMPLEMENTASI PERENCANAAN PEMBANGUNAN DAERAH BERBASIS E-PLANNING PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH (BAPPEDA) SULAWESI UTARA - Paat, Harry Patrick; Tuju, Edward Fredrik; Kalalo, Meily Y. B. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
As per Permendagri No. 86 of 2017 concerning Procedures for Regional Development Planning, good and effective management of Regional Development can increase the rate of economic growth and community welfare. For this reason, the Government through the Regional Planning and Development Agency (BAPPEDA) of North Sulawesi Province as part of the Regional Organization (OPD) is an element of planning for regional government organizers and has the task of assisting the Governor in the preparation and implementation of regional policies regional development planning. The purpose of this study is to evaluate and analyze the results of the preparation of planning documents and inputting RPJMD, Renstra, RKPD and E-planning based Renja as mandated in Ministerial Regulation number 86 of 2017 through the preparation stages of preparation, drafting, drafting, implementing Musrenbang, final draft formulation and stipulation. The method applied is the guideline for operating the annual parameter e-planning module by the Deputy for Supervision of Regional Financial Management. The results of this study indicate that BAPPEDA of North Sulawesi Province has implemented the mandate of Permendagri No. 86 of 2017, but have not optimized the use of e-planning applications. For this reason, the future BAPPEDA of North Sulawesi Province can improve its performance through e-planning.